Evolutionary Humanoid Robotics - Eaton, Malachy (Springer, 2015)
This book examines how two distinct strands of research on autonomous robots, evolutionary robotics and humanoid robot research, are converging. The book will be valuable for researchers and postgraduate students working in the areas of evolutionary robotics and bio-inspired computing.